Design and implementation of jerk-controlled elevator systems using S-curve motion profiles - Ali, Ali Abdulkareem; Salem, Fatma Ben; Mohammed, Jamal A.-K. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Electric elevators often experience significant jerks that can shorten their lifespan and cause passenger discomfort, especially during acceleration and deceleration. To address this issue, this study presents the development and implementation of S-curve motion profiles for a prototype three-floor rope elevator system. The elevator cabin is driven by a three-phase induction motor using sensorless vector control technology, with a variable frequency drive (VFD) managing the cabin's velocity. The findings indicate that employing S-curve motion profiles reduces jerk by approximately 29.43% when the elevator is ascending without a load and by 48.15% when descending without a load. In the loaded scenario, the elevator experiences a significant reduction in jerk, decreasing by 48.78% during ascent and 52.08% during descent. By smoothing out abrupt acceleration changes, the reduction in jerk leads to a more seamless motion of the elevator car, significantly enhancing passenger comfort. Consequently, this approach improves the efficiency and reliability of elevator operations, providing a versatile platform for future vertical transportation advancements.